Pengaruh Citra Merek, Komunikasi Pemasaran, Dan Inovasi Terhadap Loyalitas Konsumen Cadbury Di Kota Batam - Teresia Veronika Simamora; Hikmah Hikmah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The chocolate sector in Indonesia has rapidly transformed, driven by evolving formulations that cater to local tastes and preferences. To meet diverse consumer needs and enhance satisfaction, the chocolate industry, particularly Cadbury, continues to innovate in product formulation, flavor, and packaging. This study evaluates the impact of brand image, marketing communication, and innovation on consumer loyalty to Cadbury in Batam. Using a descriptive quantitative methodology, the study targets customers aged 17 and above who have purchased Cadbury chocolate at least twice in Batam City. With an indeterminate population size, the Jacob Cohen formula determined a sample size of 204 respondents. Data was collected through Google Forms and processed using SPSS, including descriptive tests, validity tests, reliability tests, multicollinearity tests, heteroscedasticity tests, coefficient of determination tests, t-tests, and F-tests. Results show that brand image positively and significantly affects customer loyalty. Marketing communication also has a significant positive impact, while innovation plays a crucial role. The combined influence of brand image, marketing communication, and innovation highlights the multifaceted nature of consumer loyalty, with each factor uniquely contributing to overall loyalty.